TEKNIK PENYUNTINGAN GAMBAR DENGAN MENCIPTAKAN KESINAMBUNGAN GAMBAR DALAM FILM PENDEK “SRIHUNNING KANTHIL” - Fauzzi, Mochammad Rizki (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACTThe making of this work aims to describe the work of editors in films relating tothe post-production process, including Logging, Offline Editing, Online Editing, Mixing,Distribute. As for the background for the making of the short film